Alternative agreement in Danish—mismatch without intervention - Christensen, Ken Ramshøj; Nyvad, Anne Mette (Frontiers in Language Sciences, 2025)
This study investigates “alternative agreement” in Danish, where predicative adjectives sometimes agree with the object of a preposition (P-Obj) rather than the subject. Unlike English “mismatch agreement” Danish alternative agreement occurs without linear intervention between the competing elements. Three experiments examine this phenomenon: two sentence-completion tasks (with fronted vs. in-situ P-Obj) and an acceptability judgment task. Results show that alternative agreement occurs significantly more frequently with singular P-Obj than plural P-Obj, and more frequently with fronted P-Obj than in-situ P-Obj. Standard agreement is consistently rated more acceptable than alternative agreement, though fronting increases the acceptability of alternative agreement. We argue that Danish alternative agreement results from two independent factors: (1) the phonological tendency to drop inflectional endings (apocope), affecting singular and plural P-Obj differently, and (2) the cognitive preference to interpret sentence—initial nominal elements as subjects, creating processing bias favoring agreement with fronted P-Obj. Rather than reflecting a new agreement system or language change, Danish alternative agreement appears to be a systematic performance error.